Terrorism Law Enforcement in Indonesia: Integrating Pancasila in The Fight Against Modern Threats - Muhamad Zarkasih; Sri G M Hatta; Timbo Mangaranap Sirait; Wagiman Wagiman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The evolving threat of terrorism in Indonesia has led to the development of counterterrorism laws aimed at combating both domestic and international terrorist activities. Since the Bali bombings in 2002, Indonesia has enacted a series of legal frameworks, such as Law No. 15 of 2003 and its amendments through Law No. 5 of 2018. However, these laws have raised significant concerns about human rights violations, especially regarding the treatment of detainees, preventive detention, and arbitrary arrests. This study adopts a qualitative research methodology, combining doctrinal legal analysis and empirical data gathered from interviews with legal experts, policymakers, and practitioners. It critically examines the compatibility of Indonesia’s counterterrorism laws with international human rights standards, focusing on their implementation, particularly in relation to the fundamental values of Pancasila—the state ideology of Indonesia, which emphasizes social justice, unity, and human dignity. The results highlight several key challenges, such as the need for stronger oversight mechanisms, more effective deradicalization programs, and a comprehensive approach to online radicalization. The study concludes with recommendations for integrating Pancasila principles more thoroughly into counterterrorism strategies, strengthening international cooperation, and ensuring that security measures do not infringe upon individual rights. By addressing these issues, Indonesia can enhance the effectiveness of its counterterrorism efforts while adhering to its commitment to human rights and social justice.